Bodies in nature: Associations between exposure to nature, connectedness to nature, and body image in U.S. adults. (September 2016) - Swami, Viren; Barron, David; Weis, Laura; Furnham, Adrian
Highlights: Connectedness to nature (CNS) and nature exposure is associated with body appreciation. Self-esteem mediates these relationships in women and men. Relationship between nature exposure and body appreciation is mediated by CNS. Additional mediational relationships found in men but not in women. Abstract: Here, we sought to replicate previous work showing a relationship between connectedness to nature and body appreciation, and extend it by examining associations between exposure to natural environments and other body image-related variables. An online sample of 399 U.S. women and men ( M age = 34.55 years) completed measures of body appreciation, connectedness to nature, nature exposure, appearance investment, sociocultural attitudes towards appearance, and self-esteem. Path analysis showed that nature exposure and connectedness to nature, respectively, were associated with body appreciation in women and men, both directly and indirectly via self-esteem. Connectedness to nature also mediated the link between nature exposure and body appreciation. In men, but not women, the link between connectedness to nature and body appreciation was also mediated by appearance investment and internalisation of a muscular ideal. These results may point to novel methods for promoting more positive body image in adults through engagement with nature.